Makna Sosial Religius dalam Tradisi Ziarah Makam Mbah Boyo Patih di Desa Medang Glagah Lamongan - Nikmah, Sya'idatun; Mukit, Abdul (Postgraduate Studies UIN Sunan Ampel Surabaya, 2025)
This research focuses on examining the pilgrimage tradition to the tomb of Mbah Boyopatih among the Muslim community in Medang Village, Glagah District, Lamongan. The main problems addressed in this study are: 1) What is the history of Mbah Boyopatih? and 2) What motivates visitors to perform pilgrimage to the tomb of Mbah Boyopatih? This study employs a qualitative approach with descriptive analysis, aiming to gain a comprehensive understanding of the pilgrimage tradition through data collected by observation, interviews, and documentation. The findings of this research conclude that the tomb of Mbah Boyopatih is highly venerated due to the great contributions of the Waliyullah and his extraordinary karomah (spiritual charisma). Mbah Boyopatih was a disciple of Kanjeng Sunan Giri. Within the site, there is a sacred spring known as jublang or a catfish pond, which is believed to cure various illnesses, especially skin diseases, through the consumption of the catfish. The community has sanctified the catfish as a form of respect for Mbah Boyopatih and his struggles in spreading Islam. The motivation for visiting the tomb lies in fulfilling values deeply embedded in the worldview of the community, including the belief that the spirit of the saint continues to protect the surrounding environment.